2020
DOI: 10.15252/embr.202050069
|View full text |Cite
|
Sign up to set email alerts
|

Extensive flavivirus E trimer breathing accompanies stem zippering of the post‐fusion hairpin

Abstract: Flaviviruses enter cells by fusion with endosomal membranes through a rearrangement of the envelope protein E, a class II membrane fusion protein, into fusogenic trimers. The rod-like E subunits bend into "hairpins" to bring the fusion loops next to the C-terminal transmembrane (TM) anchors, with the TM-proximal "stem" element zippering the E trimer to force apposition of the membranes. The structure of the complete class II trimeric hairpin is known for phleboviruses but not for flaviviruses, for which the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 63 publications
(130 reference statements)
1
14
0
Order By: Relevance
“…Likewise, the mutants were still capable of displaying those acidic-pH-triggered conformational changes that convert metastable E dimers into stable trimers and are necessary for membrane fusion during virus entry. These data are consistent with experiments that showed that the stem region is not involved in the stabilization of the E-trimer [13] and a study with a W421I SVP mutant of TBEV that was not only able to form stable post-fusion trimers, but also to fuse efficiently with liposomes [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Likewise, the mutants were still capable of displaying those acidic-pH-triggered conformational changes that convert metastable E dimers into stable trimers and are necessary for membrane fusion during virus entry. These data are consistent with experiments that showed that the stem region is not involved in the stabilization of the E-trimer [13] and a study with a W421I SVP mutant of TBEV that was not only able to form stable post-fusion trimers, but also to fuse efficiently with liposomes [25].…”
Section: Discussionsupporting
confidence: 91%
“…This structural element consists of two or three mostly amphipathic helices (H1, H2, H3) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] and is located between the E-ectodomain and the viral membrane ( Figure 1 A). Two regions in E are highly conserved, the fusion loop (FL) at the tip of DII and the so-called conserved sequence in the stem (CS, amino acids 420–425 in TBEV, [ 13 ]) that forms a loop between H2 and H3 ( Figure 1 A). The FL is crucial for mediating fusion during virus entry after virus uptake by receptor-mediated endocytosis [ 14 ], but the role of CS is less clearly defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conserved linear fusion loop epitope (FLE) is readily exposed on the immature structure and is poorly presented on the mature virion [ 18 ]. The mature virion undergoes dynamic E dimer ‘breathing’, a process in which the tip of EDII hinges at the EDI–EDII interface at biological temperatures, causing increased fusion loop exposure [ 19 , 20 , 21 ]. Antibodies to the fusion loop epitope are often weakly cross-neutralizing and are broadly cross-reactive [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only one of the three stem-anchor regions in the trimer is shown in panels (C) and (D).Colour code E as in Figs.1 and 2. Molecular structures shown in panel A were generated with PyMol (https://pymol.org/2) using coordinates of TBEV (PDBs: 1URZ, 6S8C[27,31]).…”
mentioning
confidence: 99%